The hydroxylase inhibitor DMOG attenuates endotoxic shock via alternative activation of macrophages and IL-10 production by B-1 cells. - FALLON, PADRAIC; HAMS, EMILY; SAUNDERS, SEAN (My University, 2011)
Localized tissue hypoxia is a feature of infection and inflammation, resulting in the upregulation of the transcription factors HIF-1? and NF-?B via inhibition of oxygen sensing hydroxylase enzymes. Previous studies have demonstrated a beneficial role for the hydroxylase inhibitor dimethyloxallyl glycine (DMOG) in inflammatory conditions, including experimental colitis, by regulating the activity of HIF-1 and NF-?B. We have demonstrated in vivo that pre-treatment with DMOG attenuates systemic LPS-induced activation of the NF-?B pathway. Furthermore, mice treated with DMOG had significantly increased survival in LPS-induced shock. Conversely, in models of polymicrobial sepsis, DMOG exacerbates disease severity. DMOG treatment of mice promotes M2 polarization in macrophages within the peritoneal cavity, resulting in the downregulation of pro-inflammatory cytokines such as TNF?. In addition, in vivo DMOG treatment upregulates IL-10 expression, specifically in the peritoneal B-1 cell population. This study demonstrates cell type specific roles for hydroxylase inhibition in vivo and provides insight into the mechanism underlying the protection conveyed by DMOG in models of endotoxic shock.
PUBLISHED
Keywords: Immunology and Infection; hydroxylase; Immunology, Inflammation & Infection